Bacterial Communities in Ground-and Surface Water Mixing Zone Induced by Seasonal Heavy Extraction of Groundwater. Issue 9 (21st October 2018) - Lee, Ji-Hoon; Lee, Bong-Joo; Unno, Tatsuya
ABSTRACT: The water curtain (WC) system has been applied to the greenhouse agricultural practice as an additional heat source during the cold season in South Korea. Thus, heavy groundwater extraction induces a drawdown of the groundwater level and an influx of adjacent surface water into the aquifers. Along with many reports on physicochemical transitions caused by groundwater–surface water mixing, not much knowledge exists about the resulting possible shifts and/or transitions of the subsurface and/or groundwater microbial community structures. Here, we studied a WC system's active site during a winter season to evaluate potential shifts of microbial community structures across the groundwater and surface water by next generation sequencing in combination with conventional physicochemical monitoring of groundwater. We found that there were shifts of groundwater microbial communities at groundwater (WJ-1 and WJ-2) near the adjacent stream, but there was a relatively delayed response of the community in the groundwater (WJ-3) located at some distance from surface water despite proximity to the wells of heavy groundwater extraction.